Social Identity and Attitudes Toward Cultural Diversity: A Cultural Psychological Analysis - Hamamura, Takeshi (Sage Publications, 2017)
Prior research indicates that there may be a disharmonious relationship between positive attitudes toward ethnic and cultural diversity and social identity within a socially dominant group. Recent work in cultural psychology, however, has implied that this disharmonious relationship may be confined to a specific representation of social identity. This research examined this possibility. Study 1 (N = 51,238) found that the negative association between national identity and diversity attitudes found among participants from Western societies did not extend to participants from non-Western societies. Study 2 (N = 222) recruited American and Japanese participants, disentangled two distinct representations of their social identity—collective and relational social identity—and found their differential associations with positive attitudes toward multiculturalism. Implications are discussed.